Endoscopic Laryngopharyngeal Surgery Combined with Endoscopic Submucosal Dissection as a Treatment Option for Superficial Hypopharyngeal Cancer with Suspected Synchronous Lymph Node Metastasis - Shinya Sugimoto; Tomohito Fuke; Daisuke Kobayashi; Mamika Kaneko; Taishi Temma; Tatsuma Nomura; Nobuyuki Tsuda; Mayu Kawabata; Ryutaro Matsushima; Hirohisa Hisada; Satoshi Hayashi; Toji Murabayashi; et al. (Case Reports in Gastroenterology, 2023)
We report 4 cases of hypopharyngeal cancer preoperatively suspected with synchronous lymph node metastases. Pathologic lymph node metastasis was confirmed in three of the four cases. All 4 cases underwent endoscopic laryngopharyngeal surgery (ELPS) combined with endoscopic submucosal dissection (ESD) and subsequent lymph node dissection as an optional treatment rather than the standard treatment. Peroral resection for primary site was selected because of the expected decline in quality of life (QoL) after radical surgery. Among 4 patients, one developed local recurrence; however, the other three remained recurrence-free and survived without any additional treatment. Furthermore, the patient who developed local recurrence had a recurrence-free survival for more than 5 years, with additional chemoradiation therapy. No disorders in speech, swallowing, or breathing was observed during the follow-up period. ELPS combined with ESD is generally indicated for laryngopharyngeal cancer without synchronous lymph node metastasis. However, this can be a treatment option for patients may wish to preserve a greater QoL after treatment. In the future, when more data on the results and long-term prognosis of this treatment are accumulated, it may be possible to discuss its validity further.